MEDIATION SYSTEM IN DISPUTES OF OWNERSHIP PERSFECTIVE ACADEMIC ISLĀḤ (A Research in Aceh Besar) - Riadhus Sholihin; Oktavi Maulizar (Universitas Islam Negeri Ar-Raniry, 2020)
This article will explain how the authority of village officials in resolving disputes over ownership of aid houses is mediated? To answer the problem above, the writer uses the descriptive analysis research method, where the data obtained is sourced from observations, interviews, photoshoots, document analysis, and field notes compiled by the writer at the research location which is not set forth in the form of figures. From the results of the study it can be seen that based on Aceh Qanun Number 9 of 2008 concerning the Development of Customary Life and Customs where village officials have the authority to reconcile disputes that occur within the community by deliberation / mediation and one of the village apparatuses that mediates the parties who disputes to end their disputes peacefully. The consequence of the mediation decision is the termination of the dispute that occurred and the parties agreed to make peace by making a peace agreement and carrying out the agreement accordingly. The concept of mediation in positive law is no different from the concept of iṣlāḥ in Islamic law which involves a third party to reconcile the disputing parties. The content of the agreement of the mediation that has been carried out by the parties, is allowed in Islamic law because the purpose of iṣlāḥ or mediation is to end the dispute.